Protecting Yourself from Online Fraud and Hacking: An Islamic Perspective - Ahyani, Hisam; Lousada, Sérgio António Neves; Sartono, Sartono; Kotyazhov, Andrey; Huda , Miftakhul (Abdurrauf Journal of Islamic Studies, 2025)
In today's digital era, online fraud and smartphone hacking have become widespread threats, compromising personal security and privacy. This article explores the concept of Hifdzul Mal (protection of wealth) in Islamic law and its relevance in safeguarding personal data and assets from cybercrimes. The purpose of this study is to examine various online fraud schemes, such as WhatsApp scams and fake job offers, and to identify the signs of smartphone hacking, while analyzing these issues within the framework of Islamic legal principles. Using a descriptive methodology, the article outlines preventive measures to protect against these risks. The findings emphasize that Islamic teachings strongly advocate for the preservation of wealth and personal information, prohibiting fraud and theft. This study contributes to understanding how the principle of Hifdzul Mal can be applied to modern digital threats, encouraging ethical behavior and ensuring personal security in the virtual world. [Di era digital saat ini, penipuan online dan peretasan smartphone semakin marak dan menjadi ancaman serius terhadap keamanan serta privasi pribadi. Artikel ini membahas konsep Hifdzul Mal (perlindungan harta) dalam hukum Islam dan bagaimana prinsip ini relevan untuk melindungi data pribadi dan aset dari kejahatan dunia maya. Penelitian ini bertujuan untuk mengeksplorasi berbagai jenis penipuan online, seperti penipuan WhatsApp dan tawaran pekerjaan palsu, serta mengenali tanda-tanda peretasan smartphone. Semua ini dianalisis dengan perspektif hukum Islam. Artikel ini menggunakan pendekatan deskriptif untuk menyarankan langkah-langkah pencegahan yang dapat diambil untuk melindungi diri dari ancaman tersebut. Temuan menunjukkan bahwa ajaran Islam sangat menekankan pentingnya melindungi harta dan informasi pribadi, serta melarang segala bentuk penipuan dan pencurian. Penelitian ini memberikan wawasan tentang bagaimana prinsip Hifdzul Mal dapat diterapkan dalam menghadapi ancaman digital modern, dan mendorong perilaku etis serta menjaga keamanan pribadi di dunia maya].